2011
DOI: 10.1051/0004-6361/201015837
|View full text |Cite
|
Sign up to set email alerts
|

A line-confusion limited millimeter survey of Orion KL

Abstract: Aims. We present a study of the silicon-bearing species detected in a line-confusion limited survey towards Orion KL performed with the IRAM 30-m telescope. The analysis of the line survey is organized by families of molecules. Our aim is to derive physical and chemical conditions for each family taking all observed lines into account from all isotopologs of each species. The large number of transitions in different vibrationally excited states covered by our data, which range from 80 to 280 GHz, let us provid… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
92
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(101 citation statements)
references
References 104 publications
8
92
1
Order By: Relevance
“…Consistently, Tercero et al (2011) showed that the 29 SiO v = 0 J = 5-4 line is contaminated by the following molecules: the hydrogen-sulfide isotopologue 34 SH 2 , the methyl-cyanide isotopologue 13 CH 3 CN, and sulfur-monoxide (SO). Beuther et al (2005) imaged the (19 6,19 -18 6,18 ) 13 CH 3 CN line at 339 137 GHz, which clearly peaks both at the hot core and IRc7 positions.…”
Section: The V = 0 29 Sio Emissionmentioning
confidence: 85%
“…Consistently, Tercero et al (2011) showed that the 29 SiO v = 0 J = 5-4 line is contaminated by the following molecules: the hydrogen-sulfide isotopologue 34 SH 2 , the methyl-cyanide isotopologue 13 CH 3 CN, and sulfur-monoxide (SO). Beuther et al (2005) imaged the (19 6,19 -18 6,18 ) 13 CH 3 CN line at 339 137 GHz, which clearly peaks both at the hot core and IRc7 positions.…”
Section: The V = 0 29 Sio Emissionmentioning
confidence: 85%
“…But especially interesting is the obtained D/H ratio (0.015), which is similar to that for dark clouds, like the ratio obtained by Langer et al (1980) in TMC1, D/H = 0.02−0.08. Table 8 shows the derived molecular abundances of HC 3 N, HC 5 N, and DC 3 N with respect to hydrogen in each component (see Tercero et al (2011) for the assumed values of N H 2 ). We found that the highest abundance of HC 3 N is obtained in the high-velocity plateau, whereas in the hot core this abundance is twice as low.…”
Section: Isotopic and Molecular Abundancesmentioning
confidence: 99%
“…Thanks to the new laboratory frequencies provided above, we have detected the two 18 O isotopologues of HCOOCH 3 in the IRAM 30 m line survey of Orion KL presented in Tercero et al (2010Tercero et al ( , 2011. After summarizing the observations, data reduction, and overall results of that line survey (Sect.…”
Section: O-hcooch 3 Detection In Orion Klmentioning
confidence: 99%
“…These components are characterized by different physical and chemical conditions (Blake et al 1987;Blake et al 1996;Tercero et al 2010Tercero et al , 2011: (i) a narrow or "spike" (∼4 km s −1 line-width) component at v LSR 9 km s −1 delineating a north-to-south extended ridge or ambient cloud (T k 60 K, n(H 2 ) 10 5 cm −3 ); (ii) a compact and quiescent region, the compact ridge, (v LSR 8 km s −1 , Δv 3 km s −1 , T k 110 K, n(H 2 ) 10 6 cm −3 ) identified for the first time by Johansson et al (1984); (iii) the plateau, a mixture of outflows, shocks, and interactions with the ambient cloud (v LSR 6−10 km s −1 , Δv 25 km s −1 , T k 150 K, n(H 2 ) 10 6 cm −3 ); (iv) a hot core component (v LSR 5 km s −1 , Δv ∼ 10 km s −1 , T k 225 K, n(H 2 ) 5 × 10 7 cm −3 ) first detected in ammonia emission Morris et al (1980). Methyl formate (in general, organic saturated O-rich molecules) emission comes mainly from the compact ridge component.…”
Section: O-hcooch 3 Detection In Orion Klmentioning
confidence: 99%
See 1 more Smart Citation